2020
DOI: 10.15244/pjoes/111240
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Applications and Bio-Profiling of <i>Tribulus Terrestris</i>: an Ecofriendly Approach

Abstract: The antibacterial and antioxidant activity of different parts of Tribulus terrestris, such as leaves and roots, was carried out using methanol and n-hexane as solvents. The leaves of plant have greater extraction yield than roots. The antibacterial activity was checked against both gram positive bacteria (Staphylococcus aureus) and gram negative bacteria (Escherichia coli). Antibacterial activity was performed by disk inhibition method. Leaves show greater antibacterial activity (29 mm and 30 mm) against both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…In the present study, it can be stated that higher antioxidant activity of T. terrestris methanol extract in all three assays is due to the presence of the phenolic and flavonoid contents. Lately, a direct relation between total phenolic contents and antioxidant activity has been shown by Arshad et al (2020) [ 44 ]. In brief, the leaves of methanol extract of T. terrestris outlined 73% inhibition in the DPPH assay as compared to 52% inhibition of root extract, which also offered more affinity towards total phenolic (723 mg GAE/g) and flavonoid (476 mg QE/g) extraction than root extract recorded with total phenolic and flavanoid contents of 235 mg GAE/g, and 93 mg QE/g, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it can be stated that higher antioxidant activity of T. terrestris methanol extract in all three assays is due to the presence of the phenolic and flavonoid contents. Lately, a direct relation between total phenolic contents and antioxidant activity has been shown by Arshad et al (2020) [ 44 ]. In brief, the leaves of methanol extract of T. terrestris outlined 73% inhibition in the DPPH assay as compared to 52% inhibition of root extract, which also offered more affinity towards total phenolic (723 mg GAE/g) and flavonoid (476 mg QE/g) extraction than root extract recorded with total phenolic and flavanoid contents of 235 mg GAE/g, and 93 mg QE/g, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Plants have an abundance of natural antioxidant compounds (secondary metabolites), which consists of variety of phytochemicals. Studies revealed that consumption of diet rich in antioxidants reduced the cardiovascular disease, neurodegenerative disease and cancer incidences [6][7][8]. The phenolic compounds have promising potential in health as nutritional supplements, herbal medicines and ROS-related disease as chemo preventive agents.…”
Section: Introductionmentioning
confidence: 99%
“…But when concentration increase from 20 to 40 mg/mL the viability of brines shrimps also decreased up to 60%, it is concluded that some bioactive compounds bind with silver particle and easily cross the cell lining and reduces the viability of larvae. The plants were good candidate for anti-cancer research on the basis of their behavior of toxicity to brine shrimp [1,12,[22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…This attribute of garlic is because of so many properties with biological application that have been reported. These properties may include antimicrobial, antioxidant, immunomodulatory, anticancer, antiinflammatory, hypoglycemic and cardiovascular effects [1][2][3]. One of the most plenteous class of organosulfur compounds, present in recently sliced or crumpled garlic is found to be responsible for the health benefits associated with garlic consumption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation